GENERATOR TEKA TEKI SILANG MENGGUNAKAN ALGORITMA GENETIKA DAN MULTITHREADING UNTUK MENGHITUNG FITNESSNYA - Widodo, Donny Kurniawan (PROXIES, 2017)
Crossword is a word game where the player must form a word by answering a clue. There are some difficulties in making crossword, such as forming word that intersects with other words. This project intends to develop a crossword generator using steady-state Genetic Algorithm. The crossword is generated based on a set of words and clues from user input. Multithreading is implemented in the fitness value calculation to speed up the calculation process. The best result can be found in the first generation but can also be found after hundreds of generation because of the randomness in the initial population.